TVE “Águila Roja” Series’ Audience Measurement Perspective (2009-2012) - Barrientos Bueno, Mónica (2014)
“Águila Roja”, Globomedia’s TV series broadcasted by the Spanish public national wide television TVE (Televisión Española), has been turned into an interesting audience phenomenon in the last years in Spain; that’s the reason why it has been made a distributive audience research, a way to make inquiries about this TV series evolution from February 2009 to January 2012 with audience’s average, golden minute and share data comparisons by seasons and episodes. At the same time this information has been set in the environment in which the episodes were broadcasted to get a global wide vision.